2020
DOI: 10.1155/2020/8797284
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Analgesic Effect of Arachic Acid Ethyl Ester Isolated from Propolis

Abstract: Inflammatory diseases are a real public health problem worldwide. Many synthetic drugs used in the treatment of inflammatory diseases such as steroidal anti-inflammatory drugs, nonsteroidal anti-inflammatory drugs (NSAIDs) and immunosuppressive drugs have harmful side effects. However, there are natural products like propolis, which is traditionally used in the treatment of pain. The objective of this work was to evaluate the anti-inflammatory and analgesic activities of the ethyl ester of arachic acid, a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Investigational studies have shown that propolis composition varies according to geographic location, botanic origin, and bee species [3,4]. Over 300 chemical components were identified in propolis, such as phenolic acids, flavonoids, and terpenes; these compounds are the most important contributors to the biological activity of propolis [5], including analgesic and anti-inflammatory effects [6,7] and antimicrobial, antioxidative, immunomodulatory, anti-diabetic and anti-tumor activities [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Investigational studies have shown that propolis composition varies according to geographic location, botanic origin, and bee species [3,4]. Over 300 chemical components were identified in propolis, such as phenolic acids, flavonoids, and terpenes; these compounds are the most important contributors to the biological activity of propolis [5], including analgesic and anti-inflammatory effects [6,7] and antimicrobial, antioxidative, immunomodulatory, anti-diabetic and anti-tumor activities [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Brazilian propolis exhibited anti-nociceptic effect and reduced paw oedema via activating the opioid receptors in rats [166]. Arachidonic acid ethyl ester, a bioactive substance isolated from Cameroonian propolis, reduced acute central pain sensation [167]. Propolis and its chemical constituents presented antinociceptive action on inflammatory and neurogenic pain without motor side effects [168].…”
Section: Analgesic Effectsmentioning
confidence: 99%
“…A number of phytochemical constituents were identified in differents propolis samples such as chalcones and dihydrochalcones [176,177], flavanones, flavones and flavonols, hydrocarbons esters ethers, terpenoids, lignans, steroids [49,178]. Brazilian red and, green propolis, Chinese propolis, Bulgarian propolis, Iranian propolis and Cameroonian propolis have the ability to reduce pain sensation in mice/rat models [165,167,169,170]. Brazilian propolis suppressed acetic acidinduced pain and increased the pain threshold reducing the nociceptive response [160].…”
Section: Analgesic Effectsmentioning
confidence: 99%
“…Furthermore, it is also reported that propolis may have several enzymes, such as adenosine triphosphate, succinic dehydrogenase, acid phosphatase, and glucose phosphatase [4,18]. Propolis has also been studied to have potential antibacterial capacity [7,14,20,21,22], antifungal [23,24,25], antiviral [7,19], antiparasitic [7,19], antioxidant [7,19,27,28,29,30], anti-cancer [7,19,32], anti-inflammatory [7,19,26], antiulcer and antidiabetic effects [7,19].…”
Section: Figmentioning
confidence: 99%